REAL-TIME STRESS ASSESSMENT USING SLIDING WINDOW BASED CONVOLUTIONAL NEURAL NETWORK - NAQVI, SYED FARAZ (2021)
Mental stress has been identified as a significant cause of several bodily disorders, such as depression, hypertension, neural and cardiovascular abnormalities. Early stress assessment is critical in order to address and avoid further health abnormalities. Conventional stress assessment methods, i.e. one-to-one interview sessions, questionnaires and self-reporting, are highly subjective, tedious, and tend to lack accuracy. Therefore, an automatic computer-aided diagnosis (CAD) method is required for accurate and timely stress assessment. Machine-learning (ML)-based computer-aided diagnosis systems can be used to assess the mental state with reasonable accuracy.